N, P and K use efficiency and maize yield responses to fertilization modes and densities - Guang-hao LI; Qian CHENG; Long LI; Da-lei LU; Wei-ping LU (Journal of Integrative Agriculture)
Optimal planting density and proper fertilization method are important factors to improve maize yield and nutrient utilization. A two-year (2016 and 2017) field experiment was conducted with three plant densities (6.0, 7.5 and 9.0 plants m–2) and three fertilization modes (no fertilizer, 0F; one-off application of slow-released fertilizer, SF; twice application of conventional fertilizer, CF). Results indicated that the grain yields and N, P and K use efficiencies under SF with the optimal planting density (7.5 plants m–2) were the highest among all the treatments in 2016 and 2017. Compared with CF, SF could increase post-silking dry matter accumulation and promote N, P and K uptake at pre- and post-silking stages; this treatment increased grain N, P and K concentrations and resulted in high N, P and K use efficiencies. Nutrient (N, P and K) absorption efficiencies and partial productivity, and nutrient (N and P) recovery efficiency in SF treatment were significantly higher than those in CF treatments under the planting density of 7.5 plants m–2. Under both SF and CF conditions, the grain yield, total N accumulation and nutrient use efficiencies initially increased, peaked at planting density of 7.5 plants m–2, and then decreased with increasing plant density. Based on the yield and nutrient use efficiency in two years, plant density of 7.5 plants m–2 with SF can improve both the grain yield and N, P and K use efficiency of spring maize in Jiangsu Province, China.